The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.geoforum.2008.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the red light district: Still neglected, immoral and marginal?

Abstract: Twenty years ago, Ashworth et al (1988) offered a distinctive and innovative interpretation of a neglected aspect of the urban scene: the red-light district. Focusing on the location of female prostitution in a series of Western European cities, their paper suggested that the geographies of sex work are revealing of some of the 'less obvious' social and political processes that shape urban space. Here, we revisit Ashworth et al's paper in the light of subsequent developments in the organisation of commercial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 48 publications
0
32
0
2
Order By: Relevance
“…From this literature we know that the environment and spaces in which sex work happens has an intrinsic bearing on the safety of those who work there. From studies of the 'red light district' (Maher 1997;Hubbard and Whowell 2008), to intricate assessments of the organisation of the indoor sex markets (Sanders 2005;Prior and Hubbard 2013), the experiences of sex workers are different depending on the locations of their work, although the mode of governance obviously has a bearing on safety first and foremost. Above I have demonstrated how research evidence shows the dangers of the street environment: this is partly because workers in a criminalised environment inhabit spaces which are dark, dangerous, out-of-sight, hidden from the general public, exposed to other criminalised street environments (namely drug markets), and occupy mainly nocturnal hours.…”
Section: Environment and Spacementioning
confidence: 99%
“…From this literature we know that the environment and spaces in which sex work happens has an intrinsic bearing on the safety of those who work there. From studies of the 'red light district' (Maher 1997;Hubbard and Whowell 2008), to intricate assessments of the organisation of the indoor sex markets (Sanders 2005;Prior and Hubbard 2013), the experiences of sex workers are different depending on the locations of their work, although the mode of governance obviously has a bearing on safety first and foremost. Above I have demonstrated how research evidence shows the dangers of the street environment: this is partly because workers in a criminalised environment inhabit spaces which are dark, dangerous, out-of-sight, hidden from the general public, exposed to other criminalised street environments (namely drug markets), and occupy mainly nocturnal hours.…”
Section: Environment and Spacementioning
confidence: 99%
“…Starting with the work of Lindberg and Distal (1985), Jehu et al (1988) and Finkelhor (1988), the literature has developed to include survivor accounts (Malone et al 1996) In the past twenty years her call has been partially answered, with a few geographical studies touching on the role CSA plays in discourses of power. Most recently this has focused on the enrolment of CSA in socially conservative, far right discourses about the dangerous, potentially-paedophile other (Ruddick 2007b;Caluya 2011;Cooper 2011;Ghertner 2011;Howlett et al 2011;Howitt et al 2012) and in the control of the spaces of sex work (Hubbard 2005;Hubbard and Whowell 2008;Mai 2013;Yea, 2013). It is also present in studies that examine the silencing of those who protect children from harm, including sexual abuse (Ruddick 2007a).…”
Section: Long-term Impacts Of Csa: Geographical Implicationsmentioning
confidence: 99%
“…As studies of prostitution and sex work have shown, not all heterosexualities are normative, hegemonic or valued. For example as research on sex workers has shown heterosexualities are often vilified, policed and persecuted for their 'inappropriate' use of space (see, for example, HUBBARD, 2000, HUBBARD and WHOWELL, 2008.…”
Section: Privilege In Geographies Of Sexualitiesmentioning
confidence: 99%